Wheat cultivar EMBRAPA 41 recommended to Minas Gerais, Goiás and Distrito Federal, Brazil - Albrecht, Julio Cesar; Andrade, José Maria Vilela de; Sousa, Cantidio Nicolau Alves de (Pesquisa Agropecuaria Brasileira, 1999)
The wheat (Triticum aestivum L.) cultivar Embrapa 41 was developed by Embrapa-Centro de Pesquisa Agropecuária dos Cerrados (CPAC), in Planaltina, DF, Brazil. This cultivar is the result of a cross between PF 813 and Polo 1 and it was evaluated in variety trials as CPAC 88118. The new cultivar was recommended by the National Commission for Wheat Research for use under irrigation during the dry season, in the states of Minas Gerais and Goiás and the Federal District. It has intermediate height, early maturity, high grain yield potential and superior industrial quality. It showed resistance to the stem rust, Puccinia graminis tritici.